Valuation of the National Agricultural Environmental Management Project’s Extensive Grassland Farming Target Project in Two Counties - Forgó, István (Acta Agraria Debreceniensis, 2004)
The National Agricultural Environmental Management Project’s (NAEMP) extensive grassland farming project is aimed at extensive cultivation on of nearly 1.1 million hectares of grassland, and at improving the state of grasslands with nature- and environment protecting methods. By using the 2002 data (the NAEMP’s first year’s data), I came to the following conclusions: Within the Extensive grassland farming project, a state subsidy was applied for on 8.94% of Hungary’s total grasslands. In Szabolcs-Szatmár-Bereg and Hajdú-Bihar counties, applied for state subsidies covered 12% of the grassland of the counties.10.45% of the projects arrived from the county of Szabolcs-Szatmár-Bereg, and 28.56% from the county of Hajdú-Bihar. In Szabolcs-Szatmár-Bereg, the support was 37.7% of the total subsidy, while in Hajdú-Bihar, it was 37.1%, unlike nationwide, which was 30.1%.The intensity of the applications is respectively 1.7 and 2.5 times more than the National (1.24) value.In my view, in some fields, which are not between nature protected areas you’d better consider permitting intensive cultivation, simultaneously with grazing, with the observation of nature- and environmental regulations.